2016
DOI: 10.1590/s0102-05362016003006
|View full text |Cite
|
Sign up to set email alerts
|

Urea concentration on vegetative development and nutrition of Cactaceae epiphytic species

Abstract: Rhipsalis paradoxa, Rhipsalis baccifera and Hatiora salicornioides are epiphytic cacti from the Atlantic Forest. They have a great ornamental potential due to the exotic characteristic of their joints (stems segments). The study aimed to evaluate the growth and development of roots and shoots as well as macronutrient and micronutrient contents in the joints of these species fertilized with different concentrations of urea as a nitrogen source. The study also analyzed the importance of the root system on nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The root number on the cuttings will increase the absorption of nutrients in plants the better cutting growth. The levels of N, P, and K in Rhipsalis plants in sand media without treatment were 1.5, 0.59, and 6.2%, respectively [30]. Rhipsalis cuttings on rice rice-hull charcoal + chopped fern had the highest total N and K levels, namely 1.71 and 8.36%, compared to other treatments.…”
Section: Discussionmentioning
confidence: 89%
“…The root number on the cuttings will increase the absorption of nutrients in plants the better cutting growth. The levels of N, P, and K in Rhipsalis plants in sand media without treatment were 1.5, 0.59, and 6.2%, respectively [30]. Rhipsalis cuttings on rice rice-hull charcoal + chopped fern had the highest total N and K levels, namely 1.71 and 8.36%, compared to other treatments.…”
Section: Discussionmentioning
confidence: 89%
“…The excess is then stored as reserve (BENZING and RENFROW, 1974;CHAPIN, 1980;VAN WIJK et al, 2003;WINKLER and ZOTZ, 2009). Other studies have reported the occurrence of luxury consumption in Cactaceae species (NOBEL and DE LA BARREA, 2002;NOBEL and LA BARRERA, 2004;TAVARES et al, 2016).…”
Section: Figure 1 Non-metric Multidimensional Scaling (Nmds) Diagrammentioning
confidence: 92%
“…Epiphytic Cactaceae species are marketed as vase plants that form an ornamental, exotic and dense mass of outstanding stems (SOUZA and LORENZI, 2000;ANDERSON, 2001;MENEGAES et al, 2015). Despite the obvious need, studies focusing on the growth and development of these species are scarce (SPURWAY and THOMAS, 1992;TAVARES et al, 2016). Suitable analytical tools to increase the knowledge of this group are also wanting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Schlumbergera truncata, little is known about its cultural requirements. Although this cactus does not have the typical requirements of most succulents, experimental work has been concentrated mainly on chemical issues (Araújo Rodrigues and Soares Queires, 2015;Tavares et al, 2016), photoperiod, and temperature manipulation (Nobel and Bobich, 2002), while other recommendations such as plant density during pot cropping are often based on the grower's experience. In general, to compensate for the low growth rate of each cactus cutting, Schlumbergera truncata growers include many phylloclades in each pot.…”
Section: Introductionmentioning
confidence: 99%